Fish Diversity and their Limnological Status of River Yamuna at Kalpi, U.P., India - Shukla, Manoj Kumar; Khare, Pushpendra Kumar; Chaurasia, Sadhana; Singh, Ravindra (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
We explore fish diversity and limnological status in the Yamuna River in Kalpi district, Uttar Pradesh, India. Several industrial and urban centers sit on the banks of the Yamuna in Uttar Pradesh. We selected four sampling stations on the Yamuna for purposes of fish fauna and water quality analysis over the course of a calendar year (October 2013 – September 2014). The samples were analyzed for selected physico-chemical analysis, and we recorded the types of fishes as well. We observed that most physico-chemical parameters were in a suitable range for the survival and growth of fish fauna. We recorded 29 species of fishes, belonging to 21 genera of 10 families.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 19Page: 57-62